2022
DOI: 10.1186/s13046-022-02510-2
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant toripalimab combined with gemcitabine and cisplatin in resectable locally advanced head and neck squamous cell carcinoma (NeoTGP01): An open label, single-arm, phase Ib clinical trial

Abstract: Background Neoadjuvant programmed death receptor-1 (PD-1) inhibitors have drawn increasing attention in locally advanced head and neck squamous cell carcinoma (HNSCC). In this study, we investigated the safety and efficacy of gemcitabine and cisplatin (GP), combined with a PD-1 inhibitor, in patients with locally advanced HNSCC. Materials and methods A total of 23 eligible patients were administered two cycles of toripalimab and GP followed by surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 50 publications
0
15
1
1
Order By: Relevance
“…Here, the reported complete response rates have increased from nivolumab (0%) 101 , nivolumab plus ipilimumab (7%) 102 , or 4% 104 to 10% in two reports combining immunotherapy with targeted therapy 111 112 . This increased further in the setting of combination with chemotherapy to 37.0% 114 , 30% 115 , 16.7% 116 , and 36.4% 117 , an assessment which is supported by a recent metanalysis of ORR comparing neoadjuvant immunotherapy to immunochemotherapy 126 .…”
Section: Open Questions and Challenges In Neoadjuvant Immunotherapymentioning
confidence: 89%
See 2 more Smart Citations
“…Here, the reported complete response rates have increased from nivolumab (0%) 101 , nivolumab plus ipilimumab (7%) 102 , or 4% 104 to 10% in two reports combining immunotherapy with targeted therapy 111 112 . This increased further in the setting of combination with chemotherapy to 37.0% 114 , 30% 115 , 16.7% 116 , and 36.4% 117 , an assessment which is supported by a recent metanalysis of ORR comparing neoadjuvant immunotherapy to immunochemotherapy 126 .…”
Section: Open Questions and Challenges In Neoadjuvant Immunotherapymentioning
confidence: 89%
“…Es gab keine Verzögerungen bei der Operation aufgrund unerwünschter neoadjuvanter Behandlungsnebenwirkungen. Über alle Kohorten hinweg lag das MPR bei 86 %, davon 67 % pathologisch vollständiges Ansprechen [116].…”
Section: Immuntherapie In Kombination Mit Anderen Wirkstoffenunclassified
See 1 more Smart Citation
“…There could be some disagreements between radiographic and pathological evaluations, which may be frequently observed in perioperative immunotherapy. A recent study by Zhigang Liu et al reported that three patients were confirmed to achieve pCR after surgery, while only one patient achieved radiographic PR according to the response evaluation criteria in solid tumors (RECIST) (23). Lee JM, et al summarized the data of pathological and radiographic response of several neoadjuvant immunotherapy clinical trials of NSCLC, demonstrating large differences in results when the two methods of evaluation were compared (24).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Zhigang Liu et al. reported that three patients were confirmed to achieve pCR after surgery, while only one patient achieved radiographic PR according to the response evaluation criteria in solid tumors (RECIST) ( 23 ). Lee JM, et al.…”
Section: Discussionmentioning
confidence: 99%